Pain experiences of men and women after cardiac surgery. Issue 19 (15th June 2016) - Bjørnnes, Ann Kristin; Parry, Monica; Lie, Irene; Fagerland, Morten Wang; Watt‐Watson, Judy; Rustøen, Tone; Stubhaug, Audun; Leegaard, Marit
Abstract : Aims and objectives: To compare the prevalence and severity of pain in men and women during the first year following cardiac surgery and to examine the predictors of persistent postoperative pain 12 months post surgery. Background: Persistent pain has been documented after cardiac surgery, with limited evidence for differences between men and women. Design: Prospective cohort study of patients in a randomised controlled trial ( N  = 416, 23% women) following cardiac surgery. Methods: Secondary data analysis of data collected prior to surgery, across postoperative days 1–4, at two weeks, and at one, three, six and 12 months post surgery. The main outcome was worst pain intensity (Brief Pain Inventory‐Short Form). Results: Twenty‐nine percent (97/339) of patients reported persistent postoperative pain at rest at 12 months that was worse in intensity and interference for women than for men. For both sexes, a more severe co‐morbidity profile, lower education and postoperative pain at rest at one month post surgery were associated with an increased probability for persistent postoperative pain at 12 months. Women with more concerns about communicating pain and a lower intake of analgesics in the hospital had an increased probability of pain at 12 months. Conclusion: Sex differences in pain are present up to one year following cardiac surgery. Strategies for sex‐targeted pain education and management pre‐ and post‐surgery may lead to better pain outcomes. Relevance to clinical practice: These results suggest that informing patients (particularly women) about the benefits of analgesic use following cardiac surgery may result in less pain over the first year post discharge.